BEBERAPA ASPEK PELAKSANAAN 'UNDERPINNING' - Indrastono Dwi Atmanto (Diponegoro University, 2012)
In areas of dense buildings often found limitations of the land, resulting in the possibility that new buildingfoundation coincides or lies below the existing foundation and excavation leads to instability of the existingfoundation. Similar problem also encountered in the construction of underground infrastructure and old buildingrestoration where the existing foundation must be strengthened. A row of bored pile or diaphragm wall arecommonly used for securing of excavation. Alternatively it is more economical to do underpinning by means ofgrouting, soil nailing and micropile, in which each method has its own advantages and disadvantages. Thesystem of underpinning provides advantages over the diaphragm wall and bored pile because it can support theload directly and saves space. This paper aims to introduce the principles of design, implementation, anticipatedactions and legal aspects of underpinning.